Research on the characteristics and protection of water hammer in long-distance dual-pipe water supply systems. - Xiaolei Zhang; Xiaoyi Guo; Yading Chen; Chen Yang; Shuyu Liu; Lixia Guo (PLoS ONE)
Hydraulic transients in long-distance pressurized water pipelines significantly impact their normal operation. This study develops a one-dimensional mathematical model for pressurized water pipelines using the method of characteristics and incorporates water hammer equations for dual-pipeline systems. The model is validated with experimental data, and simulations are conducted under real engineering conditions, focusing on valve closure operations. The analysis examines the transient responses for varying valve closure times (T) and the effect of installing surge tanks. Results show that increasing valve closure time and installing surge tanks both mitigate water hammer impacts. Specifically, when valve closure time exceeds 300 seconds, surge tanks reduce maximum pressure below the pipeline's tolerance (Pmax) and decrease the number of nodes experiencing damaging negative pressures. This model effectively simulates hydraulic transients in dual-pipeline systems and provides a foundation for developing protective measures for pipeline operations.